EFEKTIVITAS GOOGLE CLASSROOM SEBAGAI MEDIA DALAM PEMBELAJARAN JARAK JAUH DI SMK NEGERI PERTANIAN KARAWANG - Cut Putri Hadiati Sabila, - (2021)
Distance learning is the only way taken by the government to keep learning in the midst of the Covid-19 pandemic. Students of SMK Negeri Pertanian Karawang have used Google Classroom as a medium for distance learning, which has been implemented since March 2020. The obstacles faced affect the level of achievement of learning targets. Effectiveness is not only seen from the achievement of learning outcomes, but can be seen from the learning process, the availability of facilities and infrastructure and learning management. The purpose of this study was to determine the effectiveness of using google classroom in general and to determine the effectiveness of each learning indicator carried out during distance learning from January-June 2021 which was assessed by students. This research includes quantitative research with survey methods to determine the effectiveness of using google classroom in distance learning and qualitative research to interpret the meaning of the effectiveness percentage data. The results of this study indicate that the google classroom is "effective"used in distance learning with a percentage of 74%. The effectiveness of google classroom can be seen from the indicators of learning delivery that fall into the "effective" criteria getting a percentage of 73.6%, indicators of media use and interactivity that fall into the "effective" criteria getting a percentage of 73.4%, and learning evaluation indicators which include in the "effective" criteria with a percentage of 71%.